Multifunctional metal–organic frameworks-based biocatalytic platforms: recent developments and future prospects - Muhammad Bilal; Muhammad Adeel; Tahir Rasheed; Hafiz M.N. Iqbal (Journal of Materials Research and Technology, 2019)
In recent years, metal–organic frameworks (MOFs) have received accelerating research attention as a versatile carrier and promising bio-immobilization support materials for enzyme immobilization. This is particularly due to their extraordinary structural properties and multi-functionalities, such as surface area, high porosity, tunable topography, crystallinity, electronic and optical properties, thermal/chemical stability and multiple affinities (hydrophobicity and hydrophilicity). Excellent biocatalytic performance, improved stability and repeatability, high loading ability, and greater accessibility to catalytic sites are the key attributes associated with the use of novel MOF–enzyme bio-composites. This review discusses the recent developments in the use of MOFs as immobilization support materials as a platform to engineer different kinds of enzymes with requisite functionalities for biocatalysis applications in different sectors of the modern world. The second part of the review mainly focuses on MOFs-assisted immobilization strategies including surface immobilization, covalent binding, cage inclusion and in situ MOF formation and enzyme immobilization to develop enzyme–MOF bio-catalytic system. The characteristic properties rendering MOFs as interesting matrices for bio-immobilization are also presented following applications of MOFs-immobilized bio-catalyst for catalysis, sensing and detection, and protein digestion. Lastly, the review is wrapped up with conclusions and an outlook in terms of upcoming challenges and prospects for their scale-up applications. Keywords: Metal–organic frameworks, Biocatalytic system, Support materials, Immobilization strategies, Catalytic performance, Biosensing and detection